Pemanfaatan Konten Edukatif Di Youtube Untuk Pembelajaran Bahasa Inggris - Rani Dewi Yulyani (Departement of Mathematics Education, 2024)
To improve students' English language skills, innovative educational content is needed which can increase their interest and understanding of English. A way to improve English language skills is to optimize the use of information technology through various video sharing channels such as YouTube platform. The research was conducted using a qualitative descriptive approach with data collection techniques using questionnaires and interviews. The research results showed that 39 students (40.2%) of YouTube use the YouTube platform several times a week to learn English. Furthermore, it is known that the respondent's assessment criteria for the variable ability to use the internet is at 78.76 with